Is There Any Relationship between Trichomonas vaginalis Infection and Male Urethritis Risk? A Systematic Review and Meta-Analysis - Ziaei Hezarjaribi, Hajar; Saberi, Reza; Fakhar, Mahdi; Sadeghian, Najmeh (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. Male urethritis is one of the most common genital tract syndromes. Though the number of patients with urethritis is increasing worldwide, the cause of many cases of non-gonococcal urethritis (NGU) is still unknown. Objectives. This study aimed to delineate the association between Trichomonas vaginalis (T. vaginalis) infection and male urethritis. Methods. The literature was searched in PubMed, Scopus, and Web of Science databases using the search terms “urethritis,” “Trichomonas vaginalis,” “trichomoniasis,” and “male urethritis” up to February 2020. Overall risk difference(RD) was applied to assess the relationship between T. vaginalis infection and male urethritis. Results. In total, seven articles were included in this systematic review and meta-analysis study. Our meta-analysis involved the review of case-control studies, including 2,242 urethritis cases and 929 individuals as controls. Among subjects examined for trichomoniasis, in the case group, 211 males were infected, and in the control group, 32 individuals were infected. The overall risk difference (RD) was 0.06, and the total reported p value was 0.00001. Although the result of our meta-analysis was not significant, it was shown that the risk of urethritis is 0.06 more in trichomoniasis patients than in the non-exposed group. Conclusion. Findings from the included papers showed that trichomoniasis is not a risk factor for male urethritis. Although trichomoniasis alone is not the main cause of urethritis, it can be considered one of the risk factors in male urethritis. Therefore, in the future, it is necessary to perform further studies to clarify the detailed association between T. vaginalis infection and urethritis risk in male patients.